Does Suprascapular Nerve Block Improve Shoulder Disability in Impingement Syndrome? A Randomized Placebo-Contolled Study. Issue 2 (June 2014) - Barış Bayram, Korhan; Bal, Serpil; Safa Satoglu, Ismail; Kocyigit, Hikmet; Gürgan, Alev; Akcay, Serkan; Kazimoglu, Cemal
Abstract Objectives: A randomized placebo-controlled study was designed to determine the efficacy of suprascapular nerve block [SSNB] in the treatment of shoulder impingement syndrome. Methods: The study group consist of 96 patients who were randomized to an injection group [n = 51] or a placebo group [n = 45]. Patients in the group receiving active treatment had a single SSNB while patients in the control group received a placebo injection of normal saline. The evaluations were performed in terms of visual analog scale for pain intensity, and constant shoulder score [CSS] for shoulder function. Results: The SSNB group showed significant improvments compared with the placebo group with respect to pain improvment and shoulder function at the 2-week and 3-month follow-up periods. Conclusion: Suprascapular nerve block is a very effective treatment in shoulder impingement syndrome. It improves pain, disability, and range of movement at the shoulder compared with placebo.